2-biofuels (H2 and CH4) production from anaerobic digestion of biscuits wastewater: Experimental study and techno-economic analysis. (February 2021) - Tawfik, Ahmed; Ali, Manal; Danial, Amal; Zhao, Shanshan; Meng, Fangang; Nasr, Mahmoud
Graphical abstract: Highlights: The anaerobic digestion of biscuits wastewater (BW) industry was investigated. H2 yield of 118.6 mL/gCOD removed was obtained by solely anaerobic digestion of BW. OLR of 4.45 gCOD/L.d provided MY of 318.5 ± 23.5 mL/g CODt removed. HY of 414.2 ± 38.1 mL/g CODt removed was achieved at OLR exceeding 7.95 gCOD/L/d. Techno-economic study of BW treatment showed suitable payback period for investment. Abstract: The up-flow anaerobic hybrid reactor (UAHR) was simultaneously employed for 2-biofuels (H2 and CH4 ) production from solely biscuits wastewater (BW) industry and a mixture of BW with domestic sewage (DS) at a mixing ratio of 3:1 respectively. The UAHR was fed with BW and operated at an organic loading rate (OLR) of 21.9 ± 1.7 gCOD/L/d., and hydraulic retention time (HRT) of 12.0 h. The module achieved volumetric hydrogen production rate (VHPR) and hydrogen yield (HY) of 0.95 ± 0.13 L/L reactor/d., and 118.6 ± 22.3 mL/gCODremoved respectively. A substantial deterioration in the H2 productivity was occurred after 94 days of continuous-feed operation, due to the inhibition effect of long-chain fatty acids (LCFAs). DS was integrated into the BW at mixing ratio of 3.0 (BW):1.0 (DS) where the UAHR was continuously operated at OLRs of 7.95 and 4.45 gCOD/L/d., achieving H2 and CH4 yields of 414.2 ± 38.1 and 318.5 ± 23.5 mL/gCOD removed, respectively. The payback periods for the production of biogas rich CH4 and H2 were 7.1 and 5.7 y respectively.